Genomic Analysis Reveals Multi-Drug Resistance Clusters in Group B Streptococcus CC17 Hypervirulent Isolates Causing Neonatal Invasive Disease in Southern Mainland China - Campisi, Edmondo; Rosini, Roberto; Ji, Wenjing; Guidotti, Silvia; Rojas-López, Maricarmen; Geng, Guozhu; Deng, Qiulian; Zhong, Huamin; Wang, Weidong; Liu, Haiying; Nan, Cassandra; Margarit, Immaculada; et al. (Frontiers in Microbiology, 2016)
Neonatal invasive disease caused by group B Streptococcus (GBS) represents a significant public health care concern globally. However, data related to disease burden, serotype distribution and molecular epidemiology in China and other Asian countries are very few and specifically relative to confined regions. The aim of this study was to investigate the genetic characteristics of GBS isolates recovered from neonates with invasive disease during 2013-2014 at Guangzhou and Changsha hospitals in southern mainland China. We assessed the capsular polysaccharide (CPS) type, pilus islands (PIs) distribution and hvgA gene presence in a panel of 26 neonatal clinical isolates, of which 8 were recovered from Early Onset Disease (EOD) and 18 from Late Onset Disease (LOD). Among 26 isolates examined, five serotypes were identified. Type III was the most represented (15 cases), particularly among LOD strains (n=11), followed by types Ib (n=5), V (n=3), Ia (n=2) and II (n=1). We performed whole-genome sequencing (WGS) analysis and antimicrobial susceptibility testing on the 14 serotype III isolates belonging to the hypervirulent Clonal Complex 17 (serotype III-CC17).The presence of PI-2b alone was associated with 13 out of 14 serotype III-CC17 strains. Genome analysis led us to identify two multi-drug resistance gene clusters harbored in two new versions of integrative and conjugative elements (ICEs), carrying five or eight antibiotic resistance genes, respectively. These ICEs replaced the 16 kb-locus that normally contains the PI-1 operon. All isolates harboring the identified ICEs showed multiple resistances to aminoglycoside, macrolide and tetracycline antibiotic classes. In conclusion, we report the first whole-genome sequence analysis of 14 GBS serotype III-CC17 strains isolated in China, representing the most prevalent lineage causing neonatal invasive disease. The acquisition of newly identified ICEs conferring multiple antibiotic resistances could in part explain the spread of this specific clone among Chinese neonatal isolates and underlines the need for a constant epidemiological surveillance.